Reflections on `Gujarat Pradesh' of `Hindu Rashtra' - Balagopal, K. (2002)
The economic relation between the adivasis and the Muslims in rural north Gujarat is of the kind that most radical analysts have deemed to be sufficient to justify a violent class struggle. And that is just how the VHP is likely to project it as in the coming days - an explanation for adivasi participation in the violence that could be quite embarrassing for radical analysis. It is time for radical analysts to give up simplistic assumptions and modes of analysis, not for the sake of the VHP, but for possible progress in human affairs. - Reproduced.
Keywords: Communal violence - India - Gujarat; Communal violence